Efficiency of Syzygium cumini Fruit Extract as a Green Corrosion Inhibitor for Low Carbon Steel in Hydrochloric Acid Solution - Ali, Nurdin; Fonna, Syarizal; Saputra, Yumaidi; Ariffin, Ahmad Kamal; Supardi, Joli (Indonesian Journal of Chemistry, 2025)
Organic plants are gaining serious attention as metal corrosion protection. As a non-toxic material, Syzygium cumini (SC) fruit extract contains antioxidant substances that can slow the corrosion rate. This research aimed to explore SC fruit extract as a green inhibitor of corrosion on AISI 1020 low carbon steel against exposure to 1 M HCl solution. SC fruit was extracted by the Soxhlet method and characterized using total flavonoids and tannins content. The inhibition systematics were analyzed using weight loss (WL), potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS) methods. The results showed that the concentration of 600 mg/L had good corrosion inhibition effectiveness with efficiency reaching 72.91 (WL), 90.26 (PDP), and 75.15% (EIS). Surface characterization was investigated using scanning electron microscopy (SEM), Fourier transform infrared (FTIR), atomic force microscope (AFM), and X-ray diffraction (XRD) analyses. After the presence of inhibitors, corrosion products and damage to the steel were minimized compared to unprotected. This was based on the activity of inhibitor reaction to form a protective film. With the implementation of this material, SC fruit extract could be used as an environmentally friendly natural inhibitor.